On the Variability of Stratification in the Freshwater-Influenced Laptev Sea Region - Janout, Markus A.; Hölemann, Jens; Laukert, Georgi; Smirnov, Alexander; Krumpen, Thomas; Bauch, Dorothea; Timokhov, Leonid (Frontiers in Marine Science, 2020)
In this paper we investigate the seasonal and spatial variability of stratification on the Siberian shelves with a case study from the Laptev Sea based on shipboard hydrographic measurements, year-round oceanographic mooring records from 2013 and 2014 and chemical tracer-based water mass analyses. In summer 2013, weak onshore-directed winds caused spreading of riverine waters throughout much of the eastern and central shelf. In contrast, strong southerly winds in summer 2014 diverted much of the freshwater to the northeast, which resulted in 50% less river water and significantly weaker stratification on the central shelf compared with the previous year. Our year-long records additionally emphasize the regional differences in water column structure and stratification, where the northwest location was well-mixed for six months and the central and northeast locations remained stratified into spring due to the lower initial surface salinities of the river-influenced water. A 26 year record of ocean reanalysis highlights the region’s interannual variability of stratification and its dependence on winds and sea ice. Prior the mid-2000s, river runoff to the perennially ice-covered central Laptev Sea shelf experienced little surface forcing and river water was maintained on the shelf. The transition toward less summer sea ice after the mid-2000s increased the ROFI’s (region of freshwater influence) exposure to summer winds. This greatly enhanced the variability in mixed layer depth, resulting in several years with well-mixed water columns as opposed to the often year-round shallow mixed layers before. The extent of the Lena River plume is critical for the region since it modulates nutrient fluxes and primary production, and further controls intermediate heat storage induced by lateral density gradients, which has implications for autumnal freeze-up and the eastern Arctic sea ice volume.